IMPLEMENTASI PROGRAM KELUARGA HARAPAN (PKH) DALAM PENANGGULANGAN KEMISKINAN DI DESA NGAGEL KECAMATAN DUKUHSETI KABUPATEN PATI TAHUN 2021 - Alfiyaturrohmah Alfiyaturrohmah; Zudi Setiawan (Spektrum, 2023)
The implementation of Program Keluarga Harapan (PKH) in Ngagel village was going well according to the PKH implementation guidelines, many people felt helped and their living expenses were reduced, especially for education and health costs. However, the Family Hope Program in Ngagel Village cannot be said to be able to reduce poverty, because there is no community economic empowerment to improve the economy. In the context of empowering the independence of PKH recipients as well as the concept of community empowerment and assistance, PKH in Ngagel village should be further improved in order to increase income and accelerate the independence of PKH participants.Keywords: Implementation, PKH, Poverty